ความสัมพันธ์ระหว่างประชาคมโคพีพอดและปัจจัยสิ่งแวดล้อม บริเวณเกาะสีชัง จังหวัดชลบุรี - วดีพร รัตนานุพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Community structure of planktonic copepods; diversity, prosome length and biovolume; in the coastal areas of Sichang Island, Chonburi province was studies in 3 years; inter-monsoon-II (October 2008), inter-monsoon-II (October and November 2011), northeast monsoon (January 2016), inter-monsoon-I (April 2016), southwest monsoon (July 2016) and inter-monsoon-II (November 2016). In copepod species; mesoplankton; was highest in 2016 (15 species), followed in 2011 (8 species) and 2008 (5 species), while microplanktonic copepod species was highest in NE monsoon (18 species). Copepod density was highest in 2016, followed in 2011 and 2008. Similar high meso-copepod density in inter-monsoon-I and SW monsoon (619-678 ind./m3). Similar low meso-copepod density in NE monsoon and inter-monsoon-II (298-397 ind./m3). Micro-copepod density was similar pattern in meso-copepod; high density in inter-monsoon-I and SW monsoon (92,417-108,142 ind./m3), while low density in NE monsoon and inter-monsoon-II (16,888-29,402 ind./m3). Prosome length and biovolume of female copepods were higher than male, except one species; Acartia erythraea was higher than female. Salinity, Total dissolved solids (TDS) and dissolved oxygen (DO) were major environmental factors influence on copepod community.